Voice and bargaining power - Gersbach, Hans; Haller, Hans (CESifo working papers, 2006)
We propose a formal concept of the power of voice in the context of a simple model where individuals form groups and trade in competitive markets. Individuals use outside options in two different ways. Actual outside options reflect the possibility to exit or to join other existing groups. Hypothetical outside options refer to hypothetical groups that are ultimately not formed. Articulation of hypothetical outside options in the bargaining process determines the relative bargaining power of the members of a group, which constitutes an instance of the power of voice. The adopted equilibrium concept endogenizes the outside options as well as the power of voice. In our illustrative example, there exists an equilibrium that uniquely determines the power of voice and the allocation of commodities.
Keywords: Arbeitspapier; Graue Literatur